2012
DOI: 10.2478/v10078-012-0021-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Loads on Stroke and Coordination Parameters During Freestyle Semi-Tethered Swimming

Abstract: The aim of this study was to analyse to what extent the use of different loads modifies freestyle stroke and coordination parameters during semi-tethered swimming, and to examine whether those changes are positive or negative to swimming performance. First, behaviour of swimming speed (v), stroke rate (SR) and stroke length (SL) with increasing loads was examined. Secondly, mean and peak speed of propulsive phases (propvmean and propvpeak) were analysed, as well as the relative difference between them (%v). Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 20 publications
3
29
0
1
Order By: Relevance
“…1). The mean V adj during the three cycles was plotted as a function of the external load (kg), and a linear regression line was established individually based on the load-velocity plot [16]. The mean V adj was selected for the analysis because it has been reported that plotting the mean velocity produces more accurate load-velocity profiles than using the maximum velocity data on land exercises [11].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…1). The mean V adj during the three cycles was plotted as a function of the external load (kg), and a linear regression line was established individually based on the load-velocity plot [16]. The mean V adj was selected for the analysis because it has been reported that plotting the mean velocity produces more accurate load-velocity profiles than using the maximum velocity data on land exercises [11].…”
Section: Discussionmentioning
confidence: 99%
“…To predict the maximum velocity and load, it is important to minimise the number of trials to avoid fatigue. It has been reported that the load-velocity relationship is expressed as a linear line with the coefficient of determination (R 2 ) of 0.98 [16], which implies that a small number of trials might be sufficient and appropriate for performance prediction. Therefore, swimmers were instructed to perform semi-tethered swimming with three different loads (1, 5, and 9 kg) with their maximum effort.…”
Section: Data Collectionmentioning
confidence: 99%
See 3 more Smart Citations